Accountability of Surabaya Government in Providing Policies to Street Coffee Seller during Covid-19 Pandemic - Margareta, Stefani; Huda, Dr. Miftakhul (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2022)
Surabaya is the largest city in East Java which is dominated by the business sector besides education. Then, it is no need to wonder that in every corner of the city, there are small community businesses as a form or means to carry on life. During Covid-19 pandemic in Surabaya, the impact was not only on the health sector but directly on the community's economy sector due to crowd restrictions and social distancing to prevent the transmission of Covid-19. This research aims to be able to find out and identify the form of guidelines that has been implemented by the Surabaya Government towards street coffee seller during Covid-19 pandemic. The research method used is by using normative legal research. The conclusion of this research is that there is guidelines that can be implemented by the Surabaya Government on the impact of covid-19 pandemic for street coffee seller in Surabaya referring to Article 53 Government Regulation No. 7/2021 concerning Ease, Protection and Empowerment of MSME Cooperatives including credit restructuring, reconstruction business, capital assistance and assistance in other forms.